Theoretical analysis of vapour refrigeration cycle with hybrid refrigerant of different types and mixing ratios (University of Thi-Qar Journal for Engineering Sciences, 2021)
In this paper analytical study has been made to investigate a hybrid refrigerant consists of different refrigerants with different mixing ratios and find out its effects on the performance of cycle and specify the best refrigerant that gives best performance and least environmental pollution. Firstly the performance of vapor compression refrigeration system has been analyzed with several different pure refrigerants( R11, R12, R13,R22,R23, R32, R41, R115, R116, R124, R125, R134a, R142a, R143a, R152a) by REFPROP software and  the values of  coefficient of performance (COP) and  mass flow rate ( ) and work in compressor (Wc) for each pure refrigerant is calculated and by use other properties for every refrigerant it  can determine the best refrigerants to make a new refrigerant that comes from mixing of two or three of pure refrigerants with best performance for example R22 and R134a with mixing ratios (25:75),(50:50),(75:25) respectively Assuming the evaporator temperature is (-10 °C) and the condenser temperature is (35 °C). The main parameters are calculated such as new refrigerant, mass flow rate and work used in compressor for various capacity in (kW). The results showed that the maximum performance recorded with R134a and the minimum value with R115 while the values of performance for their mixtures fluctuated between the maximum and minimum values for the pure refrigerants and the cause of this is due to combination of  properties as boiling point temperature and critical temperature, latent heat of vaporization, specific heat of liquid and specific volume of the vapor